A cross sectional study to assess the functioning of cold chain in a tribal district of central India - Chourasiya, Sanjay K.; Baghel, Anil S.; Verma, Arpit; Kale, Saket (International Journal Of Community Medicine And Public Health, 2018)
Background: Immunization is one of the best efforts that India is putting forward currently to fight against various vaccine preventable diseases. Cold chain maintenance is always an issue. Therefore, cold chain maintenance is a pre-requisite in the correct delivery of immunization services. Methods: A cross sectional study was conducted among 18 cold chain points (CCPs) of Jhabua district using standard Government of India (GOI) structured questionnaires. Results: Out of 18 cold chain points only 5.55% had dry room for the storage of needle, syringes and other clerical material. A separate voltage stabilizer was attached each to deep freezer and ILR at only 22% of the health centers. Only 55.55% CCPs waste disposal pit constructed as per guideline. 94.45% cold chain handlers (CCHs) knew the definition of cold chain and correct temperature range at which vaccines to be stored, whereas only 33.33% CCHs knew about Shake test. 72.23% CCHs knew how to read vaccine vial monitor (VVM) and stages of VVM correctly. Knowledge of the CCHs regarding open vial policy was poor, with only 33.33% knowing exactly, the details of open vial policy. Conclusions: The quality of immunization programme can be increased by proper maintenance of cold chain and management of vaccine logistics at every designated cold chain point. There is need to improve the knowledge level of CCHs regarding cold chain maintenances and handling practices.